RESULTS OF INNOVATIVE TECHNOLOGIES TREATMENT OF PERIODONTAL DISEASES AND MUCOUS MEMBRANES ORAL CAVITY IN CLINIC OF THERAPEUTIC STOMATOLOGY - T.O. Petrushanko; N.V. Rozkolupa; I.Y. Lytovchenko; N.V. Kotelevsky; S.Y. Chechotina (Ukrainian Medical Stomatological Academy, 2015)
One of priorities of лікувально лікувально-консультативної work of teachers of department of therapeutic stomatology of VDNZU "UMSA" there is permanent introduction in the medical process of modern innovative technologies. Traditionally on a department which works with the students of final courses of stomatological faculty, considerable attention is spared treatment of patients with the diseases of fabrics of пародонта and mucus shell of cavity of mouth (SOPR). Scientific researches of employees of department are related to development of the nosotropic going near the methods of treatment of diseases of fabrics of пародонта and SOPR on the basis of study of mechanisms of their origin and development. Dissertation researches which was executed the employees of department the last years were devoted the holiatry of patients on генералізований пародонтит and disease of SOPR on a background the concomitant diseases of internalss. The purpose of work was become by the analysis of high-quality indexes of work of teachers of department of therapeutic stomatology for 10 years concerning курації patients with the diseases of fabrics of пародонта and SOPR in intercommunication with effectiveness of introduction of own innovative науково-практичних technologies of their treatment. The use of innovative technologies in relation to the new methods of diagnostics, treatment and prophylaxis of diseases of fabrics of пародонта and SOPR allowed to heave up on a new level the indexes of лікувально лікувально-консультативної work of stomatological establishments, in that and medical base of department of therapeutic stomatology of VDNZU "UMSA". We are analyse the quantitative and high-quality indexes of medical work of teachers of department of therapeutic stomatology for 10 years in relation to the reception of пародонтологічних patients and patients by the іх changes of SOPR. The estimation of quality of work of professors, associate professors and assistants of department was conducted on the generally accepted basic indexes of work of doctor-stomatology and presented in a table and graphic arts. Thus, increase amounts sick with the defeat of fabrics of пародонта, mucus shell of cavity of mouth on a консультативному reception on the medical base of department of therapeutic stomatology needs permanent perfection of лікувально-профілактичної help such stomatological patients. Introduction of new methods and technologies of treatment of illnesses of пародонта and SOPR allows to optimize and improve quality of grant of stomatological help, especially in stomatological establishments of III- of the IV level.